Development of Kedung Aren Tourism Village to strengthen Hepisang Branding and connect MSMEs to Global Tourism : Pengabdian - Elsa Lauwingbara; Agrensia Rambu Danga Atta Kay; Arbertus Jesnawan Putra; Candra Depi; Rochmad Bayu Utomo; Prashanth Beleya; Gan Wai Jing (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The International Community Service Program in Air Kedung Aren Tourism Village was implemented to strengthen the branding of Hepisang local products and improve the connectivity of MSMEs with the tourism sector. Kedung Aren Village has great potential for water tourism and banana farming, but this has not been optimally utilized as the village's identity or as a supporting factor for tourism destinations. This activity aims to improve digital marketing capabilities, refine branding strategies, and expand the reach of product and destination promotion to the international level. The methods of service included training in digital content creation, assistance in social media management, workshops on technology-based tourism management, field surveys, and the preparation of promotional materials for domestic and international publication. The results of the activity showed an increase in the community's skills in content production, strengthening Hepisang's marketing through social media, and increasing the visibility of Kedung Aren Water Tourism Village through publications on various digital platforms. This program also opened up opportunities for international networking through promotion to communities in Malaysia and Singapore. Overall, this KKN activity succeeded in encouraging the integration of MSMEs with tourism, strengthening the village's identity, and expanding Kedung Aren's competitive potential at the national and international levels.